Reduction of Greenhouse Gases impact in the EEE Project. Issue 1 (1st November 2022) - Ripoli, C; Abbrescia, M; Avanzini, C; Baldini, L; Ferroli, R Baldini; Batignani, G; Battaglieri, M; Boi, S; Bossini, E; Carnesecchi, F; Cicalò, C; Cifarelli, L; et al.
Abstract : The whole Extreme Energy Events (EEE) array is composed of 61 telescopes installed in Italian High Schools, built and operated by students and teachers, constantly supervised by researchers. The muon telescope of the EEE Project is made by 3 Multigap Resistive Plate Chambers (MRPC). The unconventional working sites are a unique test field for checking the robustness and the low-ageing features of the MRPC technology for particle tracking and timing purposes. The MRPCs are fluxed with a standard mixture (98% C2 H2 F4 - 2% SF6 ) of greenhouse gases (GHG) phasing out of production. The EEE Collaboration is currently studying alternative mixtures environmentally and economically sustainable. The EEE Collaboration actions to reduce the Global Warming Potential (GWP) in the MRPC array of the EEE experiment are progressing.